SIKAP DAN PERILAKU PETANI DESA PEMO SEBAGAI DESA WISATA NASIONAL DALAM USAHA WISATAAGRO DI KAWASAN TAMAN NASIONAL KELIMUTU ENDE- FLORES- NTT - Imaculata Fatima (AGRICA, 2019)
The Kelimutu area has a famous panoramic beauty and is one of the wonders of the world. Various efforts have been made by the Kelimutu National Park Office to empower local communities through agro-tourism activities. Initially, the activity went well, but after two years, the effort stalled due to human resource constraints of agro-tourism farmers. This study aims to determine The attitudes and behavior of Pemo village farmers on agro-tourism, The ability of Pemo village farmers to run agro-tourism businesses, Impact for Pemo village farmers on agro-tourism businesses, The wishes of Pemo village farmers related to agro-tourism businesses, BTNK's readiness and ability to run agro-tourism businesses; and Models developed. The research method used is a descriptive method with a population of Pemo village farmers and 50 samples. Data collection techniques by questionnaire, observation, interview, and PRA. Data analysis with qualitative and quantitative analysis using correlation coefficients and simultaneous accuracy test or F test and partial t-test. In conclusion (1) Pemo residents have the attitude and behavior to agree to develop agro-tourism; (2) farmers are not able to continue the development of agrotourism because of human resource constraints; (3) Impacts which have been received by farmers are quite good economic and financial impacts; (4) Farmers want to continue to be facilitated and need assistance, facilities and infrastructure assistance for the smooth agro-tourism business, (5) BTNK is unable to meet farmers' desires due to cost constraints, (6) the models offered are re-program and re-structuring primary agro-farmer institutions.